2020
DOI: 10.1002/ange.202009834
|View full text |Cite
|
Sign up to set email alerts
|

A Diverse View of Science to Catalyse Change

Abstract: From the structure of DNA, [1] to computer science, [2] and space-station batteries, [3] several key scientific discoveries that enhance our lives today,w ere made by marginalized scientists.T hese three scientists,R osalind E. Franklin, Alan M. Turing and Olga D. Gonzµlez-Sanabria, did not conform to the cultural expectations of how scientists should look and behave.U nfortunately,m arginalized scientists are often viewed as just aresource rather than the lifeblood that constitutes science itself.W eneed to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…Publication biases highlight obstacles to research progress.-Inequality in the demography of amphibian research can sideline diverse and locally relevant viewpoints that would otherwise aid in tackling amphibian research challenges. Numerous studies published from 2016 to 2020 have shown that, as in other STEM (science, technology, engineering, and mathematics) disciplines (Huang et al, 2020;Urbina-Blanco et al, 2020;Maas et al, 2021), female authors are still underrepresented in peer-reviewed publications of amphibian biology (Rock et al, 2021). Nevertheless, the proportion of female authors in herpetological research has increased over time, from 8% in 1973, 15% in 1983-1993(Wilson, 1998) to 31% in 2010-2015and 33% in 2016-2019(Rock et al, 2021, at a remarkably constant rate (although we note that these two studies considered different datasets and journals).…”
Section: Discussionmentioning
confidence: 99%
“…Publication biases highlight obstacles to research progress.-Inequality in the demography of amphibian research can sideline diverse and locally relevant viewpoints that would otherwise aid in tackling amphibian research challenges. Numerous studies published from 2016 to 2020 have shown that, as in other STEM (science, technology, engineering, and mathematics) disciplines (Huang et al, 2020;Urbina-Blanco et al, 2020;Maas et al, 2021), female authors are still underrepresented in peer-reviewed publications of amphibian biology (Rock et al, 2021). Nevertheless, the proportion of female authors in herpetological research has increased over time, from 8% in 1973, 15% in 1983-1993(Wilson, 1998) to 31% in 2010-2015and 33% in 2016-2019(Rock et al, 2021, at a remarkably constant rate (although we note that these two studies considered different datasets and journals).…”
Section: Discussionmentioning
confidence: 99%
“…Examples include editorials from Analytical Chemistry, 78,79 Organic Chemistry, 80 the Journal of the American Chemical Society, 81 ACS Catalysis, 82 ACS Central Science, 83 and the Journal of Chemical Education, 84 to name only a few within the ACS Publications portfolio. Fortunately, the community of journal editors has not only named the problem but many have also issued calls for actions with explicit recommendations for moving forward.…”
Section: Accounts Of Chemical Research Pubsacsorg/accounts Articlementioning
confidence: 99%
“…To reach this goal, the first step is to recover the balance between physical and spiritual needs in science. the eEndless frontierFrontier";("科学:无尽的前沿",以下简称"布什报告")。在 2021 年,中信出版集团出版了含有美国科学促进会前首席执行官 Holt 长篇导读的"布什 报告"的中文译版本 [1] 。的"布什报告"在该中译本所附的一篇中文评论中,吴军博士有 这样一个评价:"如果要在美国历史上只选一个人,对美国的科研整体贡献最大,这个人 就是范内瓦•布什。如果只选一份决定了美国科研决策,而且影响至今的报告,则非《科学: 无尽的前沿》莫属" [1] 。"布什报告"的核心思想是:科学进步是国家繁荣和安全所必不 [3] 。2021 年的一篇分析人类基因组文献的文章发现,这种" 大部分关注聚焦于少数基因" 的问题仍没有得到实质性的改善 [4] ;以至于该文作者明确指出:"当前生物学面临的一个 挑战是,要认清进行研究的动机是什么。研究者是应该把经费、时间及精力投入到最重要 或最紧迫的工作上,还是因为能可靠地获得资助和喝彩而投入到更多同样的工作上?" [4] 不久前,来自世界各地的 31 位科学家联合发表了一份公开信,希望科学界和科技管理 者关注边缘科学家,"大多数主流科学家--即符合主流文化所期望的科学家形象和行为 的科学家--不知道或不理解边缘科学家遇到的挑战" [5] 。笔者在这里以一个生物医学领 域的边缘科学家--匈牙利裔美国女科学家 Karikó 为例--匈牙利裔美国女科学家卡利蔻 (Karikó K)。没有她,就没有当前国际上广为采用的 mRNA 新冠疫苗。在一篇报道中这 样描写道:"她的年薪,至今没超过 6 万美元。苦熬 40 年,她的研究一直被认为是没有 希望,死路一条。没有科研经费,被解雇,被驱赶,被降职,被像虫豸一样遭到嘲笑和羞 辱 , 是 她 40 年 的 家 常 便 饭 " ( http://app.myzaker.com/news/article.php? pk=607ebd8b8e9f09376948d536&f=huangli) [6] 。即使在纯数学领域也未能免俗;北京大学 毕业的数学天才张益唐同样是一个边缘科学家,因为他选择只做最重要的数学问题的研究…”
unclassified